2021
DOI: 10.3390/molecules26144301
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials for Modulating the Aggregation of β-Amyloid Peptides

Abstract: The aberrant aggregation of amyloid-β (Aβ) peptides in the brain has been recognized as the major hallmark of Alzheimer’s disease (AD). Thus, the inhibition and dissociation of Aβ aggregation are believed to be effective therapeutic strategiesforthe prevention and treatment of AD. When integrated with traditional agents and biomolecules, nanomaterials can overcome their intrinsic shortcomings and boost their efficiency via synergistic effects. This article provides an overview of recent efforts to utilize nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 201 publications
(275 reference statements)
0
11
0
Order By: Relevance
“…Alzheimer’s disease (AD) is the most common type of dementia. The underlying mechanism explaining the neurotoxicity induced by β-Amyloid peptide (Aβ) aggregates may be oxidative stress [ 17 , 18 ]. Therefore, the inhibition of Aβ fibril formation and the decomposition of Aβ aggregates are considered an important treatment strategy for AD.…”
Section: Neuroprotective Effects: Alzheimer’s Disease and Parkinson’s...mentioning
confidence: 99%
See 1 more Smart Citation
“…Alzheimer’s disease (AD) is the most common type of dementia. The underlying mechanism explaining the neurotoxicity induced by β-Amyloid peptide (Aβ) aggregates may be oxidative stress [ 17 , 18 ]. Therefore, the inhibition of Aβ fibril formation and the decomposition of Aβ aggregates are considered an important treatment strategy for AD.…”
Section: Neuroprotective Effects: Alzheimer’s Disease and Parkinson’s...mentioning
confidence: 99%
“…Gold nanoparticles have been reported by many researchers as having the function of penetrating through the BBB. In the past, many studies have proven that the physical properties of nanogold (AuNPs) have inhibited the aggregation of Aβ peptides and the degradation of Aβ aggregates [ 16 , 18 , 19 , 20 , 21 , 22 ]. AuNPs also showed inhibition of acetylcholinesterase and butyrylcholinesterase, contributing to an anti-Alzheimer’s disease effect [ 23 ].…”
Section: Neuroprotective Effects: Alzheimer’s Disease and Parkinson’s...mentioning
confidence: 99%
“…The most widely used metallic nanoparticle owing to few unique features like inert behaviour, local surface plasmon resonance absorption, tuneable structural and chemical properties is gold nanoparticle (AuNP) [ 51–59 ]. Bare AuNPs and AuNPs modified with peptides or other therapeutic molecules are majorly used for the treatment of AD and has shown anti-fibrillation property [ 54 ]. Bastus et al showed that a combination of heat and gold nanoparticles can dissolve the amyloid deposits locally and remotely [ 55 ].…”
Section: Nanotherapeutics: a Promising Tool For The Treatment Of Alzh...mentioning
confidence: 99%
“…Inhibition of protein aggregation was regarded as one of the potential therapy strategies toward protein aggregation diseases. [42,43] Unfortunately, CR only had weak inhibition effect on protein aggregation. [26] In contrast, CDs with the nano-size structure as well as plentiful surface functional groups commonly exerted some modulation effects on protein aggregation.…”
Section: Inhibition Of Protein Aggregation By Cdsmentioning
confidence: 99%